Combinatorics of Chord Progressions - Kiefer, Peter (My University, 2012)
This study explored an overlap between combinatorics and music. The goal was to show chord progressions that are common to a specific collection of music, composer, or era.
Color poster with text and diagrams.
Keywords: Combinatorial analysis; Musical analysis; Music theory--Mathematics; Posters